PENGARUH PROGRAM EDUKASI PAKET MANAJEMEN HIPERTENSI TERHADAP KESADARAN WANITA BATAK DALAM MENGONTROL HIPERTENSI DI DESA PARSAORAN URAT - Rita Irawati Sitohang; Afnijar Wahyu (Universitas Murni Teguh, 2026)
Hypertension is a non-communicable disease and a major public health problem with increasing prevalence. Batak women are at high risk of hypertension due to dietary patterns, lifestyle, and cultural factors. Low awareness of hypertension management may increase the risk of complications; therefore, structured and continuous health education is needed. The objective is to determine the effect of a hypertension management package education program on the awareness of Batak women in controlling hypertension in Parsaoran Urat Village. This quantitative study used a pre-experimental One Group Pretest–Posttest Design. The population included all Batak women who suffered from or were at risk of hypertension in Parsaoran Urat Village, totaling 25 people and used Total sampling technique. Data were collected using questionnaires before and after the education program and analyzed using the Wilcoxon test. The results showed an increase in the level of awareness among Batak women in controlling hypertension after the education program with a p-value < 0.05 in the aspects of medication management, diet, and lifestyle, indicating a significant effect on respondents’ awareness. It is concluded that hypertension management package education program is effective in improving the awareness of Batak women in controlling hypertension and can serve as a reference for health professionals in implementing sustainable health education programs.